KEKERASAN TERHADAP ISTRI DALAM KELUARGA STUDI KASUS DI LORONG SEHE DESA LOLOWA’U KABUPATEN NIAS SELATAN - Teti Fernalis Daeli; Ayuni Damai Daeli (Inculco Journal of Christian Education, 2021)
AbstractViolence against wives in the family has a very bad impact, especially, the husband's lack of responsibility in the family, lack of understanding of the impact of drinking alcohol (tuak), not yet socialized on the prohibition of selling palm wine, and the lack of government and church roles in preventing violence in the family. The results of this study are certainly expected to contribute to science, especially in studying and handling cases of violence against wives in the family. research in obtaining accurate and objective data, namely library research, namely exploring and analyzing sources related to the research topic, from library sources to be able to build a theoretical framework, using psychological and sociocultural theories that underlie the occurrence of violence in the family. The second field research is research on the actual reality in the field, namely by conducting observations and interviews with wives as victims of violence and related parties. Every family is never free from problems after forming a family, but the journey in forming a family does not always go well, but sometimes it is colored by sharp life problems and problems that easily affect all aspects of life. Prepare a couple who will form a family or household. The church cooperates with all parties to prevent violence in the family.